PERANCANGAN 3D PRINTED TACTILE PICTURE BOOKS UNTUK ANAK-ANAK TUNANETRA BERBASIS IoT - Mahbubul Wathoni; Yasin Efendi; Nurbojatmiko Nurbojatmiko; Rabiatul Nurhasanah; Viesah Putra Alegra (Universitas Muhammadiyah Jakarta, 2023)
The development of Information and Communication Technology at this time is very rapid along with the development of computer technology which continues to increase in a short time. The integration between the components of networked computers will be able to provide quality, reliable, fast and secure functions and features in accordance with the required system. Along with the trend of using network technology that still pays attention to strategic and economic aspects for users, networked computerized systems now have a tendency to develop into systems that save resources by reducing the use of hardware.Perkembangan Teknologi Informasi dan Komunikasi pada saat ini sangat pesat seiring dengan perkembangan teknologi komputer yang terus meningkat dalam waktu singkat. Integrasi yang dimiliki antar komponennya komputer terhubung dengan jaringan akan mampu menyediakan fungsi dan fitur berkualitas, handal, cepat dan aman sesuai dengan sistem yang dibutuhkan. Seiring dengan adanya trend penggunaan teknologi jaringan yang tetap memperhatikan aspek strategis dan ekonomis bagi pengguna, sistem terkomputerisasi terhubung jaringan kini ada kecenderungan untuk berkembang menjadi sistem yang menghemat sumber daya dengan mengurangi penggunaan perangkat keras